Technologies for data semantic modelling. (2nd April 2007) - Caliusco, Maria Laura; Galli, Maria Rosa; Chiotti, Omar
The explicit modelling of data semantics promises to drive information integration technology to a new level of flexibility and automation. However, nowadays, the inclusion of semantic data modelling into information system development is constrained by the lack of a supporting tool based on appropriate technologies. Our contribution in this paper is based on the specification of modelling languages that make the task of information semantics definition friendly for people who have no background knowledge of semantic modelling techniques, proposed by artificial intelligence techniques. In addition, we present a prototype that implements these languages.